Development of Articulate Storyline-Based Media for Momentum and Impulse Material in Grade X Senior High Schools, Indonesia - Dimas Mahendra; Dewi Kgajar Fitriana; Khusaini, Khusaini; Bakhrul Rizky Kurniawan; Kormil Saputra (Tinta Emas Publisher, 2024)
This study aims to develop an android application-based learning media that is literacy-oriented on Momentum and Impulse material and can be run on most devices owned by students. The creation goes through several stages in its formation. Through an application on a computer or laptop called Articulate Storyline, it is developed in such a way as to become a learning media that can be used in everyday learning. With the development model used is the ADDIE model. This model was chosen because it has research steps that are systematically arranged. The steps of the ADDIE research and development procedure consist of five stages, namely Analyze, Design, Develop, Implementation and Evaluation. Which is intended for teachers and students of State High School (SMAN) 2 Pare and State Islamic High School (MAN) Paser with supporting data for material and media validation tests. The results of the study produced 91% for the media validation test and 83% for the results of the material validation test and it can be said that the learning media is very suitable for use. While the test results for teachers and students at MAN Paser and also SMAN 2 Pare each showed 90% and 94% for teachers and 90% and 89% for students.